El rincón de lectura en el desarrollo de la oralidad en los niños de 4 a 5 años del subnivel II del centro de educación inicial “Cesar Augusto Cháves Gavilánez”, parroquia San Pablo de Atenas, cantón san miguel, provincia bolívar, periodo 2021- 2022. - Chicaiza Moreta, Janeth Guadalupe (2022)
The purpose of the research project is to publicize the topic of the reading corner in the development of orality in children from 4 to 5 years of sublevel II of the Initial Education Center "Cesar Augusto Chaves Gavilánez", San Pablo de Atenas Parish, Cantone San Miguel, Bolívar Province, Period 2021-2022 and in turn the solution of the problem described and evidenced in the institution as it is: The scarce use of the reading corner has prevented the strengthening of language development in children, because it was analyzed that it is an essential tool so that you can communicate with the environment that surrounds you and develop in economic, political, social and economic life. Cultural because only through it can you express your ideas, knowledge, desires, feelings through the word. Therefore, to carry out the project, an investigation was carried out, a study of different bibliographic documentary sources and a detailed analysis of the two variables, the independent variable (cause) reading corner dependent variable (effect) development of oral language and the relationship Between the two variables, based on this, the investigative background was carried out because the subject was deepened and then the theoretical framework was developed, breaking down each of the variables, later based on this and the problem, the general and specific objectives were raised, likewise the work was justified by the assimilation and understanding of all the information regarding the subject and investigative problem, then the legal theory was made on laws that should be governed in the teaching-learning process by the educators, the referential theory the study of the context of the institution, Subsequently, the methodology was carried out, some types of research were taken into account, such as: for the purpose of basic, applied research, for the level of study, descriptive level, documentary, for the place of field research, the design methods for the temporal dimension, processing and analysis of the information and the schedule of activities, then techniques and instruments were applied the techniques used to collect field information will be the survey.- applied to the initial education teachers through the formulation of a questionnaire, instead participatory observation .- directed to boys and girls only from a parallel of sublevel II at ages 4 to 5 years with the observation sheet instrument. From the results obtained from each of the questions the data was processed by preparing their respective table, graph, the Analysis and interpretation was also done 14 according to what we know in theory, observation and information collected. Finally, based on these results, the pertinent conclusions were made and perfected with the elaboration of a proposal on a guide for didactic activities and their respective material that will serve to avoid any alteration and intervene in a timely manner in the stimulation of the children's language and thus the infant appropriates it, with this we contribute to future research so that they continue to provide solutions to problems present in the area of oral language in initial education. To conclude with the research task at the end of the project, important aspects are detailed that describe the biography of theories, consultations of different authors and the annexes that show the activities carried out